Fabrication of recyclable carbonized asphalt‐melamine sponges with high oil‐absorption capability. Issue 6 (24th November 2016) - Yao, Qian; Zhao, Pinhui; Li, Ru; Li, Chenze; Luo, Yi; Zhou, Guizhong; Yang, Menglong
Abstract: BACKGROUND: Selective absorption of oils by macroporous solid absorbents has been regarded as an easy, environment‐friendly and economical way to gather oils for oil–water separation, oil contamination cleanup and easy transport/storage. Cheap absorbent material with high oil‐absorption performance is a key factor to promote its large‐scale application. RESULTS: Highly oil‐absorptive and water‐repellent carbonized asphalt‐melamine sponges (AMS) have been prepared via a dip‐coated sponge carbonization process, using deoiled asphalt (DOA) as dip‐coating reagent and melamine sponge (MS) as template. By the combination of DOA‐derived surface modification and mild carbonization at 600°C, the AMS products obtained such key properties as low density, highly selective absorption of oils against water, flexibility, good fire‐resistance and thermal stability, and good recyclability. CONCLUSION: These findings indicate that AMS can be a promising oil‐absorbent material applicable to oil pollution control on a water surface. Benefiting from both cheap raw materials and facile economical manufacturing process, the approach proposed can contribute to the mass manufacturing of cheap oil‐absorbent products with high oil‐absorption performance. © 2016 Society of Chemical Industry